Spatiotemporal characterization of metals in small craft harbour sediments in Nova Scotia, Canada. (March 2019) - Zhang, Hongling; Walker, Tony R.; Davis, Emily; Ma, Guofeng
Abstract: Spatiotemporal (2001–2017) characterization of sediment metal concentrations were assessed in 31 small craft harbours (SCHs) in Nova Scotia, Canada by analyzing secondary data from government sediment assessment reports. Surficial sediment samples ( n  = 576) were collected prior to routine maintenance or constriction dredging activities. Sediment metal concentration ranges were 0.5–62 (As), 0.05–3.8 (Cd), 1–305 (Cr), 0.5–220 (Cu), 0.003–1.85 (Hg), 0.73–583 (Pb) and 5–2300 (Zn) mg/kg (dw), respectively. Most sediment metal concentrations (>56% of samples) were below low effect level and >96% were below high effect level sediment quality guidelines, suggesting limited ecological impairment to marine biota. Despite wide temporal coverage (16 years), large variation in sediment concentrations across SCHs were likely due to regular dredging activities preventing long-term accumulation of contaminants. Spatial distribution and enrichment factor results revealed that Canso was most impacted by metals, followed by Clarks Harbour. Graphical abstract: Unlabelled Image Highlights: Small craft harbours (SCHs) are crucial to the Canadian fishing industry. Metal concentrations were assessed in 31 SCHs in Nova Scotia from 2001 to 2017. Metal concentrations were compared to Canadian and US sediment quality guidelines. Few SCHs exceeded high effect SQG thresholds indicating limited risk to aquatic biota.